Physical, Chemical, Biological properties and heavy metal content in soils affected by the wastewater irrigation in Baran district of Rajasthan, India - Subhash Aswal; K.K. Yadav; D.K. Singh; H.S. Purohit; K. C. Meena; Shipra Jaiswal (Annals of Agricultural Research, 2022)
In this study, theeffects of the wastewater irrigation on physical, chemical, biological properties and heavy metal contents in soils were determinedin Anta city of Baran district of Rajasthan. The quality of wastewater irrigated soils assessed in reference to tube well water.A quarterly sampling was conducted at Anta city of Baran district at ten randomly selected sites along with reference site. The quality of both water and conditions under which water is used were varying significantly. Total 40 soil samples from wastewater and 08 from tube well irrigated sites were collected. In the soils the sand content, pH and dehydrogenase activity were decreased and porosity, EC, OC, available-NPK, SO4 , Cl- , dehydrogenase activity and heavy metal (Mn, Fe, Zn, Cu, Ni, Cd, Pb and Cr) contents were increaseddue to wastewater irrigation as compared to tube well water irrigation.A slight decrease in monsoon and increase were observed in summer. Some of parameters found above as the prescribed permission limits of Indian standards.Wastewater water contains low concentration of heavy metals but, long-term use of wastewater could accumulate significant amounts of heavy metals in soil and increased its available Cu, Cd, Pb, Cr, Ni and Zn compared with fresh water irrigated field. Therefore, there is an urgent need to conserve and protect fresh water and to use the water resource that is increasing as other sources are dwindling lower quality for irrigation during summer season.